The use of economic statistics - Blyth, Conrad Alexander (London : Allen & Unwin, 1960)
The book is an elementary introduction to the sources of economic statistics and their uses in answering economic questions
Includes bibliographical references and index.
gp 24/01/2019
Loans
Keywords: Statistics; Economics--Statistical methods; Economics, Mathematical